The disappearance of ethics: the 2021 St. Andrews Gifford lectures - O'Donovan, Oliver (The Gifford lectures, 2024)
"The 2021 Gifford Lectures by Oliver O'Donovan evaluate the state of ethics as a discipline and its relationship to theology"--